Role of nucleopolyhedroviruses (NPVs) in the management of lepidopteran pests in Asia - Rao, G.R.; Kumar, C.S.; Sireesha, K.; Kumar, P. Lava (Springer, 2015)
Lepidopteran insect pest species cause heavy damage to the crop yield annually around the globe. Baculoviruses, the nucleopolyhedroviruses and the granuloviruses, act as natural regulators of pest populations including lepidopteran pests, and their potential to be employed as insecticides is well reported. Baculovirus-based insecticides are safe to animal and human health and lack toxic residues. In the present chapter, a detailed review on the isolation, characterization, mass production techniques, diagnostic and quality control tests of these viruses, and the issues related with commercialization of baculovirus-based products is presented. Their high compatibility with other pest control strategies making them a potential candidate for use in integrated pest management is also discussed.